Room-temperature 2D semiconductor activated vertical-cavity surface-emitting lasers - Shang, Jingzhi; Cong, Chunxiao; Wang, Zilong; Peimyoo, Namphung; Wu, Lishu; Zou, Chenji; Chen, Yu; Chin, Xin Yu; Wang, Jianpu; Soci, Cesare; Huang, Wei; Yu, Ting (Nature communications, 2017)
Two-dimensional (2D) semiconductors are opening a new platform for revitalizing widely spread optoelectronic applications. The realisation of room-temperature vertical 2D lasing from monolayer semiconductors is fundamentally interesting and highly desired for appealing on-chip laser applications such as optical interconnects and supercomputing. Here, we present room-temperature low-threshold lasing from 2D semiconductor activated vertical-cavity surface-emitting lasers (VCSELs) under continuous-wave pumping. 2D lasing is achieved from a 2D semiconductor. Structurally, dielectric oxides were used to construct the half-wavelength-thick cavity and distributed Bragg reflectors, in favour of single-mode operation and ultralow optical loss; in the cavity centre, the direct-bandgap monolayer WS 2 was embedded as the gain medium, compatible with the planar VCSEL configuration and the monolithic integration technology. This work demonstrates 2D semiconductor activated VCSELs with desirable emission characteristics, which represents a major step towards practical optoelectronic applications of 2D semiconductor lasers. Two-dimensional materials have recently emerged as interesting materials for optoelectronic applications. Here, Shang et al. demonstrate two-dimensional semiconductor activated vertical-cavity surface-emitting lasers where both the gain material and the lasing characteristics are two-dimensional.